Effect of bisphosphonate Risedronate hydrogels towards number of Osteoclast during relapse tooth movement - Dr.drg. Tita Ratya Utari, Sp.Ort (International Orthodontic Congress London, 2015)
Mengetahui pengaruh hidrogel Bp-risedronate menuju jumlah osteoklas selama pergerakan gigi setelah perawatan ortodontik.